2016
DOI: 10.1002/bmc.3819
|View full text |Cite
|
Sign up to set email alerts
|

A new validated HPLC method for the determination of quercetin: Application to study pharmacokinetics in rats

Abstract: A simple, accurate, and reproducible high-performance liquid chromatography (HPLC) method has been developed and validated for the quantification of quercetin (QR) in rat plasma. The method involves a simple protein precipitation procedure to extract both QR and thymoquinone (TQ), the internal standard. The chromatographic analysis was achieved on a Shimadzu LC 20 A HPLC system equipped with a Supelcosil LC-18 T C column and an isocratic mobile phase consisting of 0.3% trichloroacetic acid in water and acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Therefore, fresh QR solutions were made in 5% Pluronic ® F127 every three days. Further, our previous studies have indicated that the oral bioavailability of QR in a SHR rat model is comparable to reported bioavailability data in humans [ 21 ]. The selection of the QR concentration in drinking water was designed to mimic the average daily servings of quercetin, i.e., clinically relevant doses, taking into consideration the average daily water intake and predicted oral bioavailability of QR.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, fresh QR solutions were made in 5% Pluronic ® F127 every three days. Further, our previous studies have indicated that the oral bioavailability of QR in a SHR rat model is comparable to reported bioavailability data in humans [ 21 ]. The selection of the QR concentration in drinking water was designed to mimic the average daily servings of quercetin, i.e., clinically relevant doses, taking into consideration the average daily water intake and predicted oral bioavailability of QR.…”
Section: Discussionsupporting
confidence: 76%
“…We employed different flavonoid/GSH ratios—from equal to a great excess of GSH. Although the total dietary flavonoid intake can be greater than GSH, the expected concentration of individual flavonoids in an organism is always much less than GSH [ 8 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (3,3′,4′,5,7-pentahydroxyflavone), a major bioflavonoid found in fruits and vegetables, exhibits unique biological properties [ 1 ]. A broad spectrum of beneficial quercetin properties, including antimutagenic, antifibrotic, antiinflammatory, antiatherogenic, and antibacterial effects, as well as its strong antioxidative capacity, is described.…”
Section: Introductionmentioning
confidence: 99%